Investigation of Customer Satisfaction Conditions of The Individuals Using Gyms - Karayol, Metin; Turhan, Muhammed Özkan; Ünver, Ramazan; Ergenekon, Berat (My University, 2020)
The aim of this study is to investigate customer satisfaction conditions of the individuals using gyms.While population of the study consists of the participants going to gyms in Bitlis, Diyarbakır and Siirt, thesample group of the study consists of 360 individuals in total who are volunteer and selected randomly amongthose participants from Bitlis (110), Diyarbakır (150) and Siirt (100). The participants have been given to“demographic information form” created by researchers and “sports managements’ customer satisfactionscale” having seven likert types and formed by 5 sub dimensions involving development sub dimensiondeveloped by Sevilmiş (2015), sports trainers sub dimension, the quality of work environment sub dimensionand satisfaction sub dimension. Customer satisfaction conditions and demographic information have beencompared. Number, percentage, average, standard deviations have been conducted as descriptive statisticalmethods in the evaluation of the data. According to the conducted normality test, in the analysis of data whichdo not show normal deviation U-test has been used to investigate whether the difference between two groupsis significant or not, and Kruskal Wallis test has been used to investigate whether the difference between theaverages of variables more than two is significant or not. In the analysis of the data, SPSS 20.0 package programhas been used and error margin has been accepted as 0.05. According to the test results, while it has not beenseen that there is a significant difference between the sub dimensions of educational background, income state, working condition and gender of the participants with the customer satisfaction condition sub dimensions, ithas been reported that there is a significant difference between the quality of work environment sub dimensionand (P>0,05) province and age variables, also the attendance condition and the quality of sports trainers andsatisfaction sub dimension (P<0,05).

Bu araştırmanın amacı fitness salonlarını kullanan bireylerin müşteri memnuniyet durumlarının incelenmesidir. Araştırmanın evrenini Bitlis, Diyarbakır ve Siirt illerindeki fitness salonlarına giden katılımcılar oluştururken, örneklem grubunu ise bu katılımcılar arasından rastgele seçilmiş gönüllü olan Bitlis (110), Diyarbakır (150) ve Siirt (100) toplam 360 kişi oluşturmuştur. Katılımcılara araştırmacılar tarafından oluşturulan ‘demografik bilgi formu’ ve Sevilmiş (2015) tarafından geliştirilen gelişim alt boyutu, spor merkezi kalitesi alt boyutu, çalışma ortamı niteliği alt boyutu, spor eğitmenleri niteliği alt boyutu ve memnuniyet alt boyutu olarak 5 alt boyuttan oluşan ve yedili likert tipi olan ‘spor işletmeleri müşteri memnuniyeti ölçeği’ yöneltilmiştir. Müşteri memnuniyet durumları ile demografik bilgiler karşılaştırılmıştır. Verilerin değerlendirilmesinde tanımlayıcı istatistiksel yöntemleri olarak sayı, yüzde, ortalama, standart sapma uygulanmıştır. Yapılan normallik testine göre normal dağılım göstermeyen verilerin analizinde, iki gurubun ortalamaları arasındaki farkın anlamlı olup olmadığını incelemek için U-testi, ikiden fazla değişkenlerin ortalamaları arasındaki farkın anlamlı olup olmadığını incelemek içinse kruskal-wallis testi kullanılmıştır. Verilerin analizinde SPSS 20.0 paket programı kullanılmış olup hata payı 0.05 olarak kabul edilmiştir. Yapılan test sonuçlarına göre katılımcıların eğitim durumu, gelir durumu, çalışma durumu ve cinsiyet değişkenleri ile müşteri memnuniyet durumu alt boyutları arasında anlamlı bir fark görülmezken, (P>0,05) il ve yaş değişkenlerinin çalışma ortamının niteliği alt boyutunda, devam durumu değişkeninin ise spor eğitmenleri niteliği ve memnuniyet alt boyutu arasında anlamlı bir fark saptanmıştır (P<0,05).
Fitness Salonlarını Kullanan Bireylerin Müşteri Memnuniyet Durumlarının İncelenmesi